The study of consumer’s behavior and perception in purchasing rice: case at Jasin, Melaka / Mohamad Zulfadzlie Mohd Zulkepli - Mohd Zulkepli, Mohamad Zulfadzlie (Faculty of Plantation and Agrotechnology, 2018)
Rice is the second important food crop in the world after wheat and Asia is the largest producer and consumer of rice. In Malaysia, rice is a staple food for Malaysians despite the introduction of other food item, rice has remained the main source of food energy for the majority the Malaysian population. The objective of the study is to determine the behavior of the Melaka’s consumer in purchasing rice, to anticipates the perception among Melaka’s consumer in purchasing rice, and to examine the relation between behavior and perception among Melaka’s consumer in purchasing rice. There are 384 respondents around Jasin had been sampled to capture the information related to this study. The sample method used is Simple Random Sampling (SRS). The independent variable are behavior and perception of consumer in purchasing rice while dependent variable is purchasing rice of consumer. There are two type of analysis testing used to achieve the objective, which are correlation analysis testing and regression analysis testing. The result of correlation show behavior is 0.570 and perception is 0. 468 have significant relation with purchasing rice of consumers. For multiple regression that show the behavior factor is more dominant compare to the perception in purchasing rice by consumers. This can conclude that behavior can play important role to change the purchasing rice by consumer.